Anxiety and Depression Prevalence in Free Clinic Patients - Kovarik, Jack; Bokelman, Macie; Smith, Margaret (Journal of Student-Run Clinics, 2024)
Background: Disparities in mental health services are often observed in under-resourced low-income communities, which are at an increased risk for compromised mental health. By surveying patients at JayDoc Free Clinic, a student-run free clinic (SRFC) in Kansas City, Kansas, this study sought to as-sess the prevalence of depression and anxiety and compare screening outcomes among various de-mographic groups seeking safety-net care. Methods: From May through November 2022, patients aged 12 and older were offered a Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and demographic survey. Demo-graphic variables included household income, gender, insurance status, and race and ethnicity. GAD-7 and PHQ-9 questionnaire scores were categorized into minimal, mild, moderate, or severe catego-ries. Relationships between demographic variables and scores on screening questionnaires were an-alyzed using multivariable analyses, with linear regression and analysis of variance one-way tests for significance (p-value <0.05). Results: Of 232 participants who consented to the study, 222 completed the GAD-7 and 228 com-pleted the PHQ-9. In comparison to 2019 United States national data, the percentage of respondents experiencing anxiety and depression was greater across all severity classifications. Approximately 18.1% reported symptoms of moderate to severe anxiety and 21.5% reported symptoms of moderate to severe depression, compared to national distributions of 6.1% and 7%, respectively. Of 232 participants, 54 completed the demographic survey. There was no correlation between PHQ-9 scores or GAD-7 scores and gender, household income, insurance status. Conclusion: While no association was identified between screening outcomes and demographic var-iables, the findings that the prevalence of anxiety and depression at JayDoc SRFC is greater than na-tional rates reaffirm the need for accessible mental health services for patients receiving care at SRFCs. This study provides insight into the status of mental health in an SRFC patient population and discusses mental health screening implementation at SRFCs.